Answer:
The equation of the exponential function will be:
Explanation:
The general exponential function is defined as
y = abˣ
Here,
a is the initial value and b is the growth factor
From the table, it is clear that the y-intercept is (0, 12). Note that the y-intercept can be determined by setting x=0 and solving for y.
here
at x=0, y=12
so a = 12
If we check the y-values, it is clear that every next value of y can be obtained by multiplying the previous y-value by 2.
In other words, the common multiplier = b = 2
Thus, the equation becomes
y = 12·(2)ˣ
Thus, the equation of the exponential function will be: